Konsepsi Kematian a la Jawa - Sumekar Tanjung (Program Studi Ilmu Komunikasi, 2013)
This articles describes important side about death in Java, especially Bejikarto society, in Yogyakarta. They looking at death is not the opposite of life. For them, death as a manifestation of the body’s extinction and the new life’s genesis that is eternity. In the Javanese culture, all of the life and death’s process had the concept and control. This article consist of four parts. First is introduction, describes the construction and an understating of God in their belief. Second, describes about death in Javanese people concept. Third is conceiving the causation of death in terms illness and medical. Fourth, is discussion about how Javanese people preserve the tradition in celebration of death.